T‐cell responses and therapies against SARS‐CoV‐2 infection. Issue 1 (27th October 2020) - Toor, Salman M.; Saleh, Reem; Sasidharan Nair, Varun; Taha, Rowaida Z.; Elkord, Eyad
Abstract: Coronavirus disease 2019 (COVID‐19) is caused by SARS‐CoV‐2, a novel coronavirus strain. Some studies suggest that COVID‐19 could be an immune‐related disease, and failure of effective immune responses in initial stages of viral infection could contribute to systemic inflammation and tissue damage, leading to worse disease outcomes. T cells can act as a double‐edge sword with both pro‐ and anti‐roles in the progression of COVID‐19. Thus, better understanding of their roles in immune responses to SARS‐CoV‐2 infection is crucial. T cells primarily react to the spike protein on the coronavirus to initiate antiviral immunity; however, T‐cell responses can be suboptimal, impaired or excessive in severe COVID‐19 patients. This review focuses on the multifaceted roles of T cells in COVID‐19 pathogenesis and rationalizes their significance in eliciting appropriate antiviral immune responses in COVID‐19 patients and unexposed individuals. In addition, we summarize the potential therapeutic approaches related to T cells to treat COVID‐19 patients. These include adoptive T‐cell therapies, vaccines activating T‐cell responses, recombinant cytokines, Th1 activators and Th17 blockers, and potential utilization of immune checkpoint inhibitors alone or in combination with anti‐inflammatory drugs to improve antiviral T‐cell responses against SARS‐CoV‐2. Abstract : This review focuses on the multi‐faceted roles of T cells in COVID‐19 pathogenesis and rationalizes their significance in eliciting appropriate antiviral immune responses in COVID‐19 patients and unexposed individuals. In addition, we summarize the potential therapeutic approaches related to T cells to treat COVID‐19 patients.